Self-Efficacy Beliefs for Technology Integration of University Students in North India: An Empirical Analysis - Amit Kumar Uniyal; Bharti Bahuguna, (Indian Journal of Management and Language (IJML), 2025)
A self efficacy belief plays an vital and inevitable role in the formation of perception, behavior, confidence throughout our life. Be it the compatibility with the technology or any another thing. Its use is ubiquitous now days. Technology has creeped and infiltrated in our every facet of life. In this Manuscript empirical analysis is done to understand the integration of the technology with the self efficacy beliefs. To measure the confidence in acceptance, understanding and use of technology in real life projects, online research papers of high index (Scopus, SCI and W.O.S) were referred for secondary data. A modified questionnaire (Ling Wang, Peggy A. Ertmer, Timothy J. Newby) was used as per the requirement of the study. Simple random sampling was used, responses were collected through goggle forms. Cronbach alpha =0.941 indicates the reliability of the scale. The analysis indicates that males and post graduate students are a bit less confident in the computer technological capabilities and strategies. Students in the age group 20-22 years are most confident in the self efficacy and belief of the technological capabilities and strategies, those below 20 years of age are highest instable for the use of technology in real life. If the belief and self efficacy is positive then the confidence in the use of technology in real life projects and in academics will be high and vice-versa. Highly positive correlated.